The Effect of Breakfast on Academic Performance among Grade 10 Students in Lapgap National High School - Busa, Mariche; Gordora, Judy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the morning meal habits of Grade 10 students at Lapgap National High School and their relationship with learning focus and academic performance. Anchored on the premise that adequate nutrition supports cognitive functioning, classroom participation, and academic outcomes, the study used a correlational research design. The respondents were 33 Grade 10 students enrolled during the academic year 2025–2026, selected through simple random sampling using a lottery method. Data were gathered through a structured questionnaire adapted and modified from validated sources, particularly validated constructs. The instrument included a Frequency and Preference Checklist and a 5-point Likert scale. Descriptive statistics and correlational analysis using Pearson’s correlation coefficient or Spearman’s rank correlation, as appropriate, were applied. Findings showed that students generally demonstrated positive morning meal habits, with an overall mean of 3.97, interpreted as “To a Great Extent.” Factors influencing breakfast consumption obtained an overall mean of 2.44, interpreted as “To a Little Extent,” while parental or guardian encouragement emerged as the strongest influence. Students also showed a high level of learning focus, with an overall mean of 3.41, interpreted as “To a Great Extent.” The study reported a statistically significant Pearson correlation coefficient of -0.985, interpreted as a very high relationship between morning meal habits and learning focus. The study concludes that consistent and nutritious breakfast consumption, supported by family involvement, contributes to students’ concentration, classroom engagement, cognitive readiness, and academic performance. It recommends strengthening daily breakfast habits, parental support, school-based nutrition education, wellness programs, and feeding initiatives. The study aligns with SDG 2, SDG 3, and SDG 4 by addressing food security, adolescent nutrition, and learning outcomes. Its sustainability impact supports public health, educational, community, and socio-economic initiatives for student well-being and academic success.
Keywords: Academic Performance; Breakfast Consumption; Classroom Engagement; Grade 10 Students; Lapgap National High School; Learning Focus; Morning Meal Habits; Nutrition Education; Parental Encouragement; School Feeding Programs